Species‐specific responses to climate change and community composition determine future calcification rates of Florida Keys reefs. (23rd September 2016) - Okazaki, Remy R.; Towle, Erica K.; van Hooidonk, Ruben; Mor, Carolina; Winter, Rivah N.; Piggot, Alan M.; Cunning, Ross; Baker, Andrew C.; Klaus, James S.; Swart, Peter K.; Langdon, Chris
Abstract: Anthropogenic climate change compromises reef growth as a result of increasing temperatures and ocean acidification. Scleractinian corals vary in their sensitivity to these variables, suggesting species composition will influence how reef communities respond to future climate change. Because data are lacking for many species, most studies that model future reef growth rely on uniform scleractinian calcification sensitivities to temperature and ocean acidification. To address this knowledge gap, calcification of twelve common and understudied Caribbean coral species was measured for two months under crossed temperatures (27, 30.3 °C) and CO2 partial pressures ( p CO2 ) (400, 900, 1300 μatm). Mixed‐effects models of calcification for each species were then used to project community‐level scleractinian calcification using Florida Keys reef composition data and IPCC AR5 ensemble climate model data. Three of the four most abundant species, Orbicella faveolata, Montastraea cavernosa, and Porites astreoides, had negative calcification responses to both elevated temperature and p CO2 . In the business‐as‐usual CO2 emissions scenario, reefs with high abundances of these species had projected end‐of‐century declines in scleractinian calcification of >50% relative to present‐day rates. Siderastrea siderea, the other most common species, was insensitive to both temperature and p CO2 within the levels tested here. Reefs dominated by this species had the most stable end‐of‐century growth. Under more optimistic scenarios of reduced CO2 emissions, calcification rates throughout the Florida Keys declined <20% by 2100. Under the most extreme emissions scenario, projected declines were highly variable among reefs, ranging 10–100%. Without considering bleaching, reef growth will likely decline on most reefs, especially where resistant species like S. siderea are not already dominant. This study demonstrates how species composition influences reef community responses to climate change and how reduced CO2 emissions can limit future declines in reef calcification.